WHEN NATIONAL STEREOTYPES BECOME A BRAND: THE CASE OF SPAIN’S DESTINATION MARKETING - Miriam Soriano Procas; Antonio Terrón Barroso (Cuadernos de Turismo)
This paper aims to explore the role that the Spanish central government seems to have historically played on the conformation of national stereotypes and clichés through the campaigns launched to promote the country as a holiday destination abroad. With this objective in mind, a qualitative analysis on the use of images associating the country and its people(s) with different forms of exoticism has been carried out. Special attention has been payed to representations of the country through soft power factors such as sun, beaches, arts or gastronomy and Spaniards through traditionalism and, more recently, through celebrities.